Comparison between acupuncture and antidepressant therapy for the treatment of poststroke depression: Systematic review and meta-analysis. Issue 22 (4th June 2021) - Zhang, Lincheng; Chen, Bing; Yao, Qigu; Chen, Weiyan; Yang, Weinan; Yang, Weiji; He, Lan; Zhang, Yuyan
Abstract: Background: In this paper, a systematic review and meta-analysis of published randomized controlled trials (RCTs) was conducted to compare the efficacies of acupuncture and antidepressant therapy for the treatment of poststroke depression (PSD). Methods: The research team searched RCTs published on PubMed; Medline; Cochrane library; Chinese National Knowledge Infrastructure (CNKI); Wanfang; Embase; Scopus, and Sinomed from their respective establishments to January 2019. We evaluated the Hamilton Depression Rating Scale (HAMD) scores, Treatment Emergent Symptom Scale (TESS) scores, National Institute of Health Stroke Scale (NIHSS) scores, and total clinical efficacy using fixed effects models. Results: Fourteen RCTs, representing a total of 1124 patients, were studied. Results showed that acupuncture was more effective in improving HAMD scores at 3 weeks after administration (mean difference [MD] = −1.17, 95%CI = −2.18 to −0.16), at 4 weeks (MD = −4.44, 95% CI = −5.64 to −3.23), at 6 weeks (MD = −1.02, 95% CI = −1.68 to −0.36), and at 8 weeks (MD = −4.33, 95% CI = −4.96 to −3.70). Similarly, acupuncture more dramatically decreased NIHSS scores (MD = −2.31, 95% CI = −2.53 to −2.09), and TESS scores (MD = −4.70, 95% CI = −4.93 to −4.48) than conventional Western medicinal therapy. Further, the total clinical efficacy in the acupuncture group was significantly higher than in the antidepressants group (risk ratio [RR] = 1.15, 95% CI = 1.08–1.21). Conclusions: The results of this study suggest that acupuncture not only can reduce the severity of PSD, but also has significant effects on decreasing the appearance of other adverse events.